(untitled) (Fiep Bulletin - online, 2014)
The initial undergraduation that comprehend a set of pedagogical, scientific and specific knowledge necessary for the teacher’s action has the objective of improvement, construction and reconstruction of the wrong knowledges and common sense that the student learned before starting the university. However, is the initial undergraduation process, the Physical Education undergraduation, obtaining this objective? The objective of this work is to analyse if occurred evolution on students thoughts after attending Physical Education undergraduation about the purpose of the teacher’s action and the knowledges necessaries for the teacher’s action when compared with initial students thoughts, concluding students, and graduated teachers that already works on school. This study is a qualitative search. For data collection were used questionnaires which were about teacher’s actions. It was applied to initial students of Physical Education course of the Universidade Estadual de Londrina, oriented by the resolutions CNE/CP 01 e 02/02, and concluding students in the same university, oriented by de CFE03/87 resolution in the Physical Education course of last tree years and teachers that work in the basic education. The thoughts of initial students and concluding students didn’t show significant changes. So the curriculum based on resolution 03/87 isn’t obtaining its objectives with the education for the initial undergraduation because of its generalist character. The continuous formation isn’t obtaining its objectives at school. One expects that the new course based on the resolution CNE/CP 01 e 02/02, reaches the objectives hoped for the school Physical Education.